Towards a Monthly Business Cycle Chronology for the Euro Area - Mönch, Emanuel (OECD Publishing, 2005)
This paper is an exercise in dating the Euro area business cycle on a monthly basis. Using a quite flexible interpolation routine, we construct several monthly series of Euro area real GDP, and then apply the Bry-Boschan (1971) procedure. To account for the asymmetry in growth regimes and duration across business cycle phases, we propose to extend this method with a combined amplitude/phase-length criterion ruling out expansionary phases that are short and flat. Applying the extended procedure to US and Euro area data, we are able to replicate approximately the dating decisions of the National Bureau of Economic Research (NBER) and the Centre for Economic Policy Research (CEPR)